2005
DOI: 10.1080/09649060500168176
|View full text |Cite
|
Sign up to set email alerts
|

Proposals to Transfer Complaints Panels to the Commission for Social Care Inspection – Throwing the Baby out with the Bath Water?

Abstract: This article considers proposed changes to the social services complaints procedure. The Health and Social Care (Community Health and Standards) Act 2003 makes provision for complaints Panels to be taken away from local authorities. The suggestion is that in future the Commission for Social Care Inspection (CSCI) should be responsible for running all Panels. We argue that this proposal is not grounded in a satisfactory rationale, is not the best solution to any concerns about Panels and could lead to problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Their findings indicate that, at this early stage in the development of the procedure, the role of the panels was not clear and was not consistent across authorities (Dean et al 1996). More recently, Ferris (2006) looked at the operation of the complaints review panel in England from the perspective of complaints officers and panel members, and concluded that review panels in England still varied from one local authority to another but that, despite this variation, they were better than the alternatives under consideration in 2005 (Williams andFerris 2005). While the research conducted by Ferris considers the value of the complaints review panel from the perspective of panel members and local authority complaints officers, very little research has considered the views of complainants.…”
Section: Existing Research On Complaints Proceduresmentioning
confidence: 99%
“…Their findings indicate that, at this early stage in the development of the procedure, the role of the panels was not clear and was not consistent across authorities (Dean et al 1996). More recently, Ferris (2006) looked at the operation of the complaints review panel in England from the perspective of complaints officers and panel members, and concluded that review panels in England still varied from one local authority to another but that, despite this variation, they were better than the alternatives under consideration in 2005 (Williams andFerris 2005). While the research conducted by Ferris considers the value of the complaints review panel from the perspective of panel members and local authority complaints officers, very little research has considered the views of complainants.…”
Section: Existing Research On Complaints Proceduresmentioning
confidence: 99%